Clinical, Electrodiagnostic, and Genetic Features of Tangier Disease in an Adolescent Girl with Presentation of Peripheral Neuropathy - Per, Huseyin; Canpolat, Mehmet; Bayram, Ayşe Kaçar; Ulgen, Ege; Baran, Burçin; Kardas, Fatih; Gumus, Hakan; Kumandas, Sefer; Bilguvar, Kaya; Çağlayan, Ahmet Okay (Neuropediatrics, 2015)
Tangier disease (TD) is a rare, autosomal recessive inherited disorder caused by a mutation in the adenosine triphosphate-binding cassette transporter 1 (ABCA1) gene, which results in a decrease in plasma high-density lipoprotein (HDL) levels. Peripheral neuropathy can be seen in approximately 50% of patients with TD, which usually occurs after the age of 15 years, and is characterized by relapsing-remitting mono- or polyneuropathy or syringomyelia-like neuropathy. Herein, we report a 16-year-old female patient who was initially diagnosed with peripheral neuropathy at the age of 13 years. Whole exome sequencing was performed, and a nonsense mutation (p.Arg1817X) in ABCA1 was identified. The patient was investigated for systemic findings of TD after the genetic diagnosis was made, and low (< 5 mg/dL) levels of HDL cholesterol were detected by lipid electrophoresis. Other family members were reexamined after the diagnosis of the proband, and asymptomatic sister of the proband was diagnosed with TD. We would like to emphasize that TD should be considered in the differential diagnosis of pediatric patients presenting with peripheral neuropathy; furthermore detection of HDL levels by lipid electrophoresis is a simple but indicative diagnostic test.
Keywords: Tangier disease; neuropathy; whole exome sequencing; ABCA1